Sertifikasi Asesor Kompetensi Guru Produktif Program Keahlian Tata Boga dalam Pelaksanaan Uji Sertifikasi Kompetensi - Nurul Farikhatir Rizkiyah; Rina Rifqie Mariana; Soenar Soekopitojo (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to describe certification of assessors and the suitability of assessors in SMKN 3 Malang in conducting competency certification tests. Source of data obtained from teachers productive culinary skills program as many as 14 people. Data collection techniques are questionnaires, interviews and documentation. Data processing technique using descriptive with qualitative and quantitative approach. The assessors of the Culinary skill program at SMKN 3 Malang from productive teachers are in compliance with the requirements as competence assessors in providing assessment to test participants on the implementation of competency certification tests. The competency assessors of Culinary skill program at SMKN 3 Malang are in the category according to the percentage of 94,73%.Abstrak: Penelitian ini bertujuan untuk mengetahui sertifikasi asesor dan kesesuaian asesor di SMKN 3 Malang dalam melaksanakan uji sertifikasi kompetensi. Sumber data diperoleh dari guru produktif program keahlian tata boga sebanyak 14 orang. Teknik pengambilan data yaitu angket, wawancara dan dokumentasi. Teknik pengolahan data menggunakan deskriptif dengan pendekatan kualitatif dan kuantitatif. Asesor pada program keterampilan Tata Boga di SMKN 3 Malang yang berasal dari guru produktif sudah sesuai dan telah memenuhi persyaratan sebagai asesor kompetensi dalam memberikan assesmen kepada peserta uji pada pelaksanaan uji sertifikasi kompetensi. Asesor kompetensi memiliki kategori sesuai dengan persentase sebesar 94,73%.